2019
DOI: 10.1242/jeb.195172
|View full text |Cite
|
Sign up to set email alerts
|

Is conservation of center of mass mechanics a priority in human walking? Insights from leg-length asymmetry experiments

Abstract: Center of mass (COM) control has been proposed to serve economyand stability-related locomotor task objectives. However, given the lack of evidence supporting direct sensing and/or regulation of the COM, it remains unclear whether COM mechanics are prioritized in the control scheme of walking. We posit that peripheral musculoskeletal structures, e.g. muscle, are more realistic control targets than the COM, given their abundance of sensorimotor receptors and ability to influence whole-body energetics. As a firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
2
2
0
Order By: Relevance
“…Notably, we observed gait changes during baseline walking (i.e. both feet moving at the same speed) with the motorized shoes that were consistent with other studies showing that shoe weight (Ochsmann et al, 2016) and height (McDonald et al, 2019) alter walking movements. In addition, the rigidity of the motorized shoes' soles (Chiou et al, 2012) is another factor that might contribute to the differences that we observed in joint angles during baseline walking.…”
Section: Study Implicationssupporting
confidence: 90%
“…Notably, we observed gait changes during baseline walking (i.e. both feet moving at the same speed) with the motorized shoes that were consistent with other studies showing that shoe weight (Ochsmann et al, 2016) and height (McDonald et al, 2019) alter walking movements. In addition, the rigidity of the motorized shoes' soles (Chiou et al, 2012) is another factor that might contribute to the differences that we observed in joint angles during baseline walking.…”
Section: Study Implicationssupporting
confidence: 90%
“…We found a few differences in joint motions when walking with our motorized shoes during regular walking, which will be useful for future designs of this portable device. Notably, we observed gait changes during baseline walking (i.e., both feet moving at the same speed) with the motorized shoes that were consistent with other studies showing that shoe weight (Ochsmann et al, 2016) and height (McDonald et al, 2019) alter walking movements. In addition, the rigidity of the motorized shoes’ soles (Chiou et al, 2012)is another factor that might contribute to the differences that we observed in joint angles during baseline walking.…”
Section: Discussionsupporting
confidence: 90%
“…They also completed a further six trials, also of 5 min duration, wearing one normal shoe and one custom-made platform-shoe with an additional foam sole attachment equal to 10.5 ± 0.5% of the participant's lower limb length (the 'perturbed' condition; modified Volley, Brand Collective, Australia; figure 1). This perturbation has previously been shown to disrupt lower limb kinematics and kinetics [18]. The total mass of the normal footwear was standardized to the platform shoe using packages of small lead weights secured to the shoe's canvas upper.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Specifically, we aimed to determine how a continuous mechanical gait perturbation, imposed through asymmetrical leg lengths, acutely impacts gait energetics and speed error regulatory performance. This perturbation was chosen as it had the potential to disrupt both energetics and speed error regulation [18], and, as such, observed behaviours could provide insight into acute multi-factor control strategies. Given that matching the treadmill's speed is a critical requirement to mitigate an immediate task-level failure, we hypothesized that the PWS in the disrupted condition would be the speed at which stride-to-stride speed errors would be most successfully regulated; therefore, speed error would be minimized by acute PWS selection in the perturbed condition as opposed to COT.…”
Section: Introductionmentioning
confidence: 99%